Endogenous intracellular calcium buffering and the activation/inactivation of HVA calcium currents in rat dentate gyrus granule cells (The Rockefeller University Press, 1991)
Granule cells acutely dissociated from the dentate gyrus of adult rat brains displayed a single class of high-threshold, voltage-activated (HVA) Ca2+ channels. The kinetics of whole-cell Ca2+ currents recorded with pipette solutions containing an intracellular ATP regenerating system but devoid of exogenous Ca2+ buffers, were fit best by Hodgkin- Huxley kinetics (m2h), and were indistinguishable from those recorded with the nystatin perforated patch method. In the absence of exogenous Ca2+ buffers, inactivation of HVA Ca2+ channels was a predominantly Ca(2+)-dependent process. The contribution of endogenous Ca2+ buffers to the kinetics of inactivation was investigated by comparing currents recorded from control cells to currents recorded from neurons that have lost a specific Ca(2+)-binding protein, Calbindin-D28K (CaBP), after kindling-induced epilepsy. Kindled neurons devoid of CaBP showed faster rates of both activation and inactivation. Adding an exogenous Ca2+ chelator, 1,2-bis-(2-aminophenoxy)ethane-N,N,N',N'-tetraacetic acid (BAPTA), to the intracellular solution largely eliminated inactivation in both control and kindled neurons. The results are consistent with the hypothesis that endogenous intraneuronal CaBP contributes significantly to submembrane Ca2+ sequestration at a concentration range and time domain that regulate Ca2+ channel inactivation.